Effect of passive control on a cell-converter system - Vidal Fuentes, José Rafael; Blé González, Gamaliel; Olmos López, José Armando (JOURNAL OF BASIC SCIENCES, 2025)
In this work, the system of a boost converter coupled with a solar cell as a power source is studied. The study is approached from the local stability analysis of the three differential equations that model the system. Then the energy shaping control based on passivity is applied to determine the global stability of the system. Using this control, the mathematical model is studied and the simulation results are compared with those obtained experimentally.